The Effect of Contrast Training on the Development of Muscular Power and Selected Physiological Indicators in Advanced Basketball Players - Mohammed, Harith Mebsher (Journal of Physical Education, 2026)
The purpose of this study was to investigate the effect of contrast training on the development of muscular power and selected physiological indicators in advanced basketball players. An experimental design with two equivalent groups was employed. The sample consisted of twelve players from Al-Difa’a Al-Jawi Basketball Club, who were randomly assigned into an experimental group (n = 6) and a control group (n = 6). The experimental group followed a contrast training program for eight weeks, with three training sessions per week, while the control group continued their regular training program. The dependent variables included muscular power tests (vertical jump and seated medicine ball throw) and selected physiological indicators (resting heart rate, systolic blood pressure, and heart rate recovery). Pre- and post-tests were conducted for both groups. The results revealed statistically significant improvements in all physical and physiological variables in favor of the experimental group compared with the control group. These findings indicate that contrast training is an effective training method for enhancing muscular power and improving cardiovascular efficiency in advanced basketball players. The study concludes that incorporating contrast training into training programs can significantly contribute to improving physical performance and physiological adaptation. Therefore, it is recommended that coaches and practitioners adopt this training method within modern training programs for competitive basketball players.